Enterprise Architecture SMA ATISA DIPAMKARA - Dedy Mulyadi (Universitas Raharja, 2024)
Enterprise architecture (EA) is a framework for designing, building, and managing information systems and information technology (IT) within an organization. This study aims to design EA at SMA Atisa Dipamkara. The research employs the TOGAF ADM method. The results of the study indicate that the design of EA at SMA Atisa Dipamkara can provide benefits for the school, namely improving the efficiency and effectiveness of school business processes, facilitating decision-making by school management, and enhancing customer satisfaction at the school.